OP0155 Development of A JAK3 Specific Inhibitor Clinical Candidate: Functional Differentiation of JAK3 Selective Inhibition over PAN-JAK or JAK1 Selective Inhibition. (15th July 2016) - Telliez, J.-B.; Wang, L.; Jussif, J.; Lin, T.H.; Li, L.; Moy, E.; Li, W.; Zhao, Y.; Crouse, K.; Symanowicz, P.; Hegen, M.; Banker, M.E.; et al.
Abstract : Background: Janus kinase (JAK) inhibitors targeting multiple JAK isoforms, JAK1 and 2, or selective against JAK1 are currently utilized in clinical practice or being developed for the treatment of various inflammatory and oncological diseases. No truly JAK3-selective inhibitor has reached the clinic. JAK3 signal in pairs with JAK1 to transduce signal elicited from six known cytokines (IL-2, IL-4, IL-7, IL-9, IL-15 & IL-21) binding to the gamma-common (g-c) chain cytokine receptors. JAK1 in addition to be required for g-c chain cytokine receptors signaling can also signal in pair with JAK2 or TYK2 and is required for other cytokine receptors signaling such as type I and II interferons and IL-6 and IL-10 families of cytokines. Other cytokines such as IL-12 and IL-23 are signaling via JAK2 and TYK2. Additionally, hematopoietic cytokines such as EPO and TPO as well as cytokines such as IL-3 and IL-5 signal via homodimers of JAK2. Objectives: Develop a JAK3 selective inhibitor that will inhibit signaling from the g-c chain cytokine receptors at therapeutic dosing without inhibiting signaling by other cytokines such as hematopoietic cytokines, type I and II interferons and IL-6, IL-12 and IL-10 families of cytokines. Methods: A JAK3-specific covalent ATP competitive inhibitor was assessed functionally in vitro and in vivo . Functional differentiation of JAK3 selective inhibition as compare to pan-JAK inhibition (tofacitinib) or JAK1 selective inhibition was also assessed. Results: The inhibitor showed JAK3 selective inhibition in biochemical and cellular assays. It inhibits Th1 and Th17 cell differentiation and function. Importantly, sparing JAK1 inhibition, through the selectivity of this inhibitor, preserved anti-inflammatory functions such as the differentiation of alternatively activated M2a macrophages. Unlike pan-JAK or JAK1-selective inhibitors, JAK3 selective inhibition also preserved IL-10-dependent suppression of the production of pro-inflammatory cytokines following LPS treatment in macrophages while maintaining the suppression of TNF and IL-1 responses in IL-27-primed macrophages. Further characterization of this compound in the rat adjuvant-induced arthritis (AIA) demonstrated efficacy at reducing disease pathology. Conclusions: We have identified the first trully selective JAK3 inhibitor with potency and properties that make it suitable for further clinical development. Disclosure of Interest: J.-B. Telliez Employee of: Pfizer, L. Wang Employee of: Pfizer, J. Jussif Employee of: Pfizer, T. Lin Employee of: Pfizer, L. Li Employee of: Pfizer, E. Moy Employee of: Pfizer, W. Li Employee of: Pfizer, Y. Zhao Employee of: Pfizer, K. Crouse Employee of: Pfizer, P. Symanowicz Employee of: Pfizer, M. Hegen Employee of: Pfizer, M. E. Banker Employee of: Pfizer, F. Vincent Employee of: Pfizer, J. Clark Employee of: Pfizer, A. Thorarensen Employee of: Pfizer